Effective Leadership in a Turbulent Organisational Environment - Syed Jamal Abdul Nasir Syed Mohamad; Georg Hauer (International Journal of Supply Chain Management, 2017)
Any organization may experience unwanted situations that lead to chaos, a downturn, or even a crisis. Because of this, leaders who are not prepared for managing a crisis situation or are leading an organization in a turbulent organisational environment will have a negative impact on the organization. Thus, the purpose of this paper is to discuss effective leadership in turbulent times. Among the approaches are the Michigan Model of Leadership and the Mindful Engagement. These frameworks act as guidance for leaders in facing todays complex and dynamic world. This paper also presents a modified framework that suggests steps to be taken by an individual into a credible leader towards future uncertainties as well as researchers for further research purposes.